2019
DOI: 10.3390/en12193763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study on Photo-Thermal Energy Conversion Performance of Functionalized and Non-Functionalized MWCNT Nanofluid

Abstract: Multiwalled carbon nanotubes (MWCNTs) have attracted attention from researchers because of their superior thermal properties and high optical absorption. In this investigation, the thermal and optical properties of functionalized and nonfunctionalized MWCNT nanofluid based on ethylene glycol/water were experimentally studied and compared. The results indicated that the use of the functionalized MWCNT nanofluid improved the thermal properties and optical absorption performance compared with the nonfunctionalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Remarkable efforts have been made to understand which nanofluid could better fit the requirements of the desired application [6,10,12,[14][15][16][17][18][19][20][21][22][23]. Concerning DASC systems, it is a hard task to find a nanofluid that provides suitable chemical, thermophysical, fluid-dynamics and optical properties at the same time, as it must work both as a heat carrier and as a light absorber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable efforts have been made to understand which nanofluid could better fit the requirements of the desired application [6,10,12,[14][15][16][17][18][19][20][21][22][23]. Concerning DASC systems, it is a hard task to find a nanofluid that provides suitable chemical, thermophysical, fluid-dynamics and optical properties at the same time, as it must work both as a heat carrier and as a light absorber.…”
Section: Introductionmentioning
confidence: 99%
“…However, some types of nanoparticles have become promising, such as the family of carbon-based nanostructures. Graphite [10,14], single and multi-walled nanotubes [12,[15][16][17][18], nanohorns [6,19,20], and graphene [21][22][23], were widely considered for solar energy applications. Carbon-based nanoadditives reach higher thermal conductivity enhancements at lower concentrations than other families of nanoparticles (metals, metal oxides).…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed the good dispersion stability of the MGE/[HMIM]BF 4 nanofluid to the good combination of the [HMIM]BF 4 ionic liquid and graphene modification. In addition, Boldoo et al [68] compared the photothermal energy conversion performance of COOH-functionalized and non-functionalized MWCNT nanofluids. They found that the COOH-functionalized MWCNT nanofluid exhibited superior photothermal energy conversion performance than the non-functionalized MWCNT nanofluid at the same nanofluid concentration owing to the enhancement of stability.…”
Section: Photothermal Energy Conversion Performance Of Nanofluidsmentioning
confidence: 99%
“…According to Dao et al [93], by widening the solar absorption spectrum of working fluids, nanoparticles showed a high potential to enhance the efficiency of solar steam generation, as shown in Figure 23. Generally, solar steam generation technologies are categorized into two groups: surface absorption [94][95][96] and volumetric absorption [66][67][68][69][70] solar steam generation. In Figure 24, Wang et al [90,97] presented a bio-inspired evaporation film from localized evaporative biological processes such as sweating and transpiration.…”
Section: Solar-driven Steam Generatorsmentioning
confidence: 99%
“…They have reported an increase of 19.85% in thermal conductivity for a volume concentration of 0.6% at 60°C compared to the base fluid. Troglbileft B et al 15 conducted a comparative study using functionalized and non‐functionalized MWCNT nanoparticles in a mixture of EG and water. They reported that the functionalized MWCNT/EG and water nanofluid showed better thermal conductivity and optical absorption properties compared to non‐functionalized MWCNT/EG water nanofluid.…”
Section: Introductionmentioning
confidence: 99%